2020
DOI: 10.1136/esmoopen-2020-000787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use and efficacy of (neo)adjuvant chemotherapy in angiosarcoma: a multicentre study

Abstract: IntroductionAngiosarcomas constitute approximately 2% to 3% of all soft tissue sarcomas, are characterised by an aggressive clinical behaviour and poor outcome. Optimal management of localised angiosarcomas consists of complete surgical resection with or without radiation. However, due to the infiltrating nature of this disease, complete resection is often not possible. Despite optimal management, the outcome of patients with localised disease remains poor. The role of (neo)adjuvant chemotherapy in angiosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“… 2 , 3 However, these reports mainly describe skin, breast, colon, or mixed tumors due to rare incidence. 1 , 4 In this report, we demonstrate the response of a patient with primary gastric angiosarcoma to doxorubicin-based NAC after three cycles. We present the following case in accordance with the CARE reporting checklist.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“… 2 , 3 However, these reports mainly describe skin, breast, colon, or mixed tumors due to rare incidence. 1 , 4 In this report, we demonstrate the response of a patient with primary gastric angiosarcoma to doxorubicin-based NAC after three cycles. We present the following case in accordance with the CARE reporting checklist.…”
Section: Introductionmentioning
confidence: 67%
“…Their results are also diverse, and generally showed poor prognosis. 4,9 Reports of cases involving other sites of angiosarcoma were reviewed. Early reports showed poor experience in management with adjuvant chemotherapy or combinations of chemotherapy and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PBT with chemotherapy followed by adjuvant chemotherapy seems to be an effective regimen in patients with cardiac angiosarcoma. Recently, a European study retrospectively examining the treatment approaches in patients with angiosarcoma reported prolonged disease‐free survival (DFS) in patients undergoing multimodality approach combining chemotherapy (neoadjuvant, adjuvant, or both), surgery, and RT 3 . The benefits of PBT in sarcoma stem from the physical characteristics of protons, which lead to improved dose conformality to the tumor volume and help in escalating the doses to the tumor while sparing the surrounding tissue 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no prospective randomized trials are available, retrospective studies have suggested that neoadjuvant systemic treatment is feasible with clinical benefit. Data from the European Organisation for Research and Treatment of Cancer (EORTC) institutions with 59 AS patients receiving neoadjuvant systemic treatment demonstrated that various systemic treatments, including chemotherapy and anti-angiogenic agents, have anti-tumour activity and could be maintained until maximum benefit; 10% of patients who received neoadjuvant treatment had disease progression before surgical intervention [ 21 ]. The median disease-free survival (DFS) and overall survival (OS) outcomes of the 86 AS patients, including the 59 patients who received neoadjuvant treatment, was 1.4 years and 4.9 years, respectively [ 21 ].…”
Section: Treatments For Localized Angiosarcomamentioning
confidence: 99%